Mainstream maverick : John Hughes and New Hollywood cinema - Chard, Holly (University of Texas Press, 2020)
"Chard examines the filmmaker Hughes's career in New Hollywood cinema and explores his ability to achieve mainstream success while maintaining creative control over his films and making his name into a brand. She uses his example to question broader understandings of how New Hollywood worked in the 1980s and 1990s and the nature of authorship in filmmaking"--